Competencias laborales de las secretarias y su influencia en la eficiencia administrativa de la Unidad Educativa Emigdio Esparza - Mantuano Zuñiga, Joselyn Mercedes (2022)
This case study focuses on the analysis of the labor skills of the secretaries and their influence on the administrative efficiency of the Emigdio Esparza Educational Unit, with which through observation and direct approach to the place where the activities are carried out of the secretaries, it was possible to witness inefficient administrative processes, being necessary for this the application of information collection tools, with which accurate data was obtained that made it possible to direct this investigation. The skills and abilities of the secretaries have not been fully applied, which is why many parents who intervene as users in this case have mentioned that they do not feel happy with the attention provided by the area of the Secretary of Instruction, all This is due to the inefficiency and poor delivery they provide, without giving a timely response to what is requested, which leads to the loss of time. That is why conclusions and recommendations are mentioned aimed at a possible solution that allows improving the actions carried out and that in turn highlights the good work of the Educational Institution, which has been characterized by its high school offers in administrative and financial areas. In the development of this document, the results obtained are detailed, as well as conceptualizations that allow clearing up questions regarding the variables under study.